2018
DOI: 10.2334/josnusd.16-0786
|View full text |Cite
|
Sign up to set email alerts
|

Effect of collagenase concentration on the isolation of small adipocytes from human buccal fat pad

Abstract: Dedifferentiated fat (DFAT) cells were isolated from mature adipocytes using the ceiling culture method. Recently, we successfully isolated DFAT cells from adipocytes with a relatively small size (<40 μm). DFAT cells have a higher osteogenic potential than that of medium adipocytes. Therefore, the objective of this study was to determine the optimal concentration of collagenase solution for isolating small adipocytes from human buccal fat pads (BFPs). Four concentrations of collagenase solution (0.01%, 0.02%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…DFAT cells from small adipocytes exhibited higher osteogenic potential than those from large adipocytes [ 54 ]. Bone regeneration involves a complex interaction between DFAT cells and biological factors [ 55 ]. DFAT cells undergo osteogenic differentiation by the stimulated of retinoic acid, an analogue of retinol that interacts with bone morphogenetic proteins (BMPs) to limit adipogenesis and promote osteogenesis [ 43 ].…”
Section: Regenerative Medicine Based On Dfat Cellsmentioning
confidence: 99%
“…DFAT cells from small adipocytes exhibited higher osteogenic potential than those from large adipocytes [ 54 ]. Bone regeneration involves a complex interaction between DFAT cells and biological factors [ 55 ]. DFAT cells undergo osteogenic differentiation by the stimulated of retinoic acid, an analogue of retinol that interacts with bone morphogenetic proteins (BMPs) to limit adipogenesis and promote osteogenesis [ 43 ].…”
Section: Regenerative Medicine Based On Dfat Cellsmentioning
confidence: 99%
“…After about 1 week, the medium was replaced with growth media, and the flasks were inverted so that the cells were on the bottom of the culture flasks ( Fig. 1) [22][23][24][25]. The initial DFAT cells, referred to as passage 0 (P0), were passaged at 80% confluence.…”
Section: Preparation Of Dedifferentiated Fat Cellsmentioning
confidence: 99%
“…Dedifferentiated fat (DFAT) cells are established by asymmetrical division of mature adipocytes from adipose tissue with a ceiling culture technique, which relies on the inherent buoyancy of adipocytes [22][23][24][25]. Unlike terminally differentiated adipocytes, DFAT cells have the potential to actively proliferate and have the characteristics of MSCs, i.e., multiple differentiation into osteoblasts [26,27], adipocytes [26,27], chondrocytes [26], skeletal myocytes [28], smooth muscle cell lineages [29,30], cardiomyocytes [31], and endothelial cells [32,33] in vitro.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DFAT cells have the characteristics of MSCs, with the multipotent capacity to differentiate into adipocytes [20][21][22], osteoblasts [20,21,23], chondrocytes [20], skeletal myocytes [24], smooth muscle cells [25,26], cardiomyocytes [27], and endothelial cells [28,29]. ASCs and DFAT cells can be isolated from subcutaneous adipose tissues or buccal fat pads [14,20,[30][31][32][33]. Recent oral and maxillofacial research has demonstrated that DFAT cells and ASCs potentially contribute to the generation of skeletal bone and periodontal tissue in animals [14,30,32,34].…”
Section: Introductionmentioning
confidence: 99%